2016
DOI: 10.1186/s12864-016-2770-7
|View full text |Cite
|
Sign up to set email alerts
|

Expanding the view on the evolution of the nematode dauer signalling pathways: refinement through gene gain and pathway co-option

Abstract: BackgroundSignalling pathways underlie development, behaviour and pathology. To understand patterns in the evolution of signalling pathways, we undertook a comprehensive investigation of the pathways that control the switch between growth and developmentally quiescent dauer in 24 species of nematodes spanning the phylum.ResultsOur analysis of 47 genes across these species indicates that the pathways and their interactions are not conserved throughout the Nematoda. For example, the TGF-β pathway was co-opted in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 37 publications
(55 citation statements)
references
References 74 publications
2
53
0
Order By: Relevance
“…Given that gene absence in a transcriptome might be simply due to expression changes, we performed an analysis (see STAR Methods) combining transcriptomic and genome data for P. pacificus [11] and P. exspectatus [12] as well as the transcriptome assembly of P. arcanus to test whether predicted losses in P. pacificus and P. exspectatus lacked orthologous sequences in genomic data. Even though further analysis will be needed to confirm gene losses in individual cases [13,14], our genome-wide analysis shows that 80% of predicted gene losses were indeed supported by genomic data ( Figure 1C). Thus, our phylotranscriptomic analysis strongly supports the conclusion of an overall higher rate of gene loss in hermaphroditic lineages as originally observed in Caenorhabditis [4,5,15].…”
Section: Resultsmentioning
confidence: 81%
“…Given that gene absence in a transcriptome might be simply due to expression changes, we performed an analysis (see STAR Methods) combining transcriptomic and genome data for P. pacificus [11] and P. exspectatus [12] as well as the transcriptome assembly of P. arcanus to test whether predicted losses in P. pacificus and P. exspectatus lacked orthologous sequences in genomic data. Even though further analysis will be needed to confirm gene losses in individual cases [13,14], our genome-wide analysis shows that 80% of predicted gene losses were indeed supported by genomic data ( Figure 1C). Thus, our phylotranscriptomic analysis strongly supports the conclusion of an overall higher rate of gene loss in hermaphroditic lineages as originally observed in Caenorhabditis [4,5,15].…”
Section: Resultsmentioning
confidence: 81%
“…Consistent with the phylogeny that underlies our study design, longer branches between extant taxa and more ancestral inner nodes (Susoy et al 2016) show higher numbers of species-specific duplications and gene losses. Because it can be difficult to differentiate true losses from missing evidence (Gilabert et al 2016;Rödelsperger 2018), the numbers of species-specific gene losses within most of the sampled Pristionchus species seem to be rather stable and only increase in the two outgroups (Fig. 1C).…”
Section: The Majority Of Gene Families Can Be Explained By a Single Ementioning
confidence: 99%
“…Within the mammals, our searches showed that RTE1 Sar is found only in S. araneus. We have previously shown that mis-assembly of the genome can be responsible for the perceived absence of a gene [23], which can also be the case for a transposon if only few, old or fragmented copies exist. Therefore, we searched for RTE1 Sar in the short sequence reads for species of the order of Eulipotyphla, for which genome projects are available: the European hedgehog Erinaceus europaeus, the Hispaniolan solenodon Solenodon paradoxus woodi and the star-nosed mole Condylura cristata, each representing a different family within the Eulipotyphyla.…”
Section: Rte-1 Sar Originates From Nematodesmentioning
confidence: 99%